Three-layered structure for sharing event information in distributed environment. (3rd August 2009) - Ikezaki, Masakazu; Watanabe, Toyohide; Ushiama, Taketoshi
We propose a three-layered structure model for handling broadly spreading geographic events successfully in the distributed environment. In our model, event data and geographic objects are represented independently in the 1st layer, and they are associated dynamically according to a query in the 2nd layer by using regular expression for attribute changes and spatio-temporal relation. In the 3rd layer, data propagated from the 2nd layer are aggregated to be used in application systems. Based on this framework, event data and geographic objects could be represented independently, and event data computed in the 2nd layer would be shared and re-used.